Cracked it! How to solve big problems and sell solutions like top strategy consultants - Garrette, Bernard (Springer International Publishing, 2018)
Solving complex problems and selling their solutions is critical for personal and organizational success. For most of us, however, it doesn't come naturally and we haven't been taught how to do it well. Research shows a host of pitfalls trips us up when we try: We're quick to believe we understand a situation and jump to a flawed solution. We seek to confirm our hypotheses and ignore conflicting evidence. We view challenges incompletely through the frameworks we know instead of with a fresh pair of eyes. And when we communicate our recommendations, we forget our reasoning isn't obvious to our audience. How can we do it better? In Cracked It!, seasoned strategy professors and consultants Bernard Garrette, Corey Phelps and Olivier Sibony present a rigorous and practical four-step approach to overcome these pitfalls. Building on tried-and-tested (but rarely revealed) methods of top strategy consultants, research in cognitive psychology, and the latest advances in design thinking, they provide a step-by-step process and toolkit that will help readers tackle any challenging business problem. Using compelling stories and detailed case examples, the authors guide readers through each step in the process: from how to state, structure and then solve problems to how to sell the solutions. Written in an engaging style by a trio of experts with decades of experience researching, teaching and consulting on complex business problems, this book will be an indispensable manual for anyone interested in creating value by helping their organizations crack the problems that matter most.